Pengaruh Penggunaan Fasilitas Online di Era Digital terhadap Literasi Perilaku Mahasiswa D3 Perbankan Angkatan 2016 Fakultas Ekonomi dan Bisnis Islam (FEBI) Universitas Islam Negeri (UIN) Raden Fatah Palembang (MOTIVASI, 2022)
The development of internet users in Indonesia continues to increase, even the increase is very sharp. From 2012 data, there were only 63 million users. However, within 6 years it has more than doubled to 143.28 million people in 2018. The development and advancement of internet technology has led to excessive use of IT among urban youth. One of them is the use of the internet to search for information that is not appropriate for age and is not carried out on the basis of certain interests (Sugihartati, 2014: 93). According to a recent survey from the Indonesian Internet Organization Association (APII) regarding penetration and behavior, information literacy and digital communication are very important to prevent internet users from the adverse effects and behavior changes of internet users. It needs support from various parties, one of which is the school. This study aims to describe and determine the negative and positive impacts on the use of online facilities by students in the D3 Banking study program, Faculty of Islamic Economics and Business Class of 2016 at Raden Fatah State Islamic University (UIN) Palembang. The research method is field survey and literature study, data collection techniques are interviews, observations and distributing questionnaires. The data analysis technique is descriptive qualitative and quantitative, primary data is processed by SPSS. The expected outcome after this research is that the University is expected to be able to literate the behavior of D3 Banking students for the 2016 Faculty of Economics and Islamic Business (FEBI) Raden Fatah State Islamic University (UIN) Palembang towards the use of online facilities.